Case studies in the management of refractory bleeding in patients with haemophilia A and inhibitors. (4th February 2013) - Valentino, L. A.; Allen, G.; Gill, J. C.; Hurlet, A.; Konkle, B. A.; Leissinger, C. A.; Luchtman‐Jones, L.; Powell, J.; Reding, M.; Stine, K.
Summary In haemophilia patients with well‐established high‐titer inhibitors, even seemingly minor acute bleeding episodes or surgical procedures may become refractory to treatment and transform into limb‐ or life‐threatening situations. In the absence of evidence‐based treatment guidelines, this article presents 10 cases of difficult to control acute and surgical bleeding and offers consensus opinions regarding their management from a panel of experienced haemophilia treaters.